Gry aksjologiczne a zarządzanie projektem informatycznym - Krupa, Marian (Annales. Etyka w Życiu Gospodarczym, 2010)
Every professionally managed project is performed accordingly to precise defined principles, methods and a plan. As well, IT projects, which are major business ventures globally these days, are governed with similar approach. Defining objectives and project framework, selecting resources, drafting schedules are a fundamental skills, which can be taught at every basic business course. It seems to be that it is enough to acquire appropriate knowledge in area of project management to be successful IT manager in spite of the size and the type of the venture. Still, only 16% ERP projects are successful, 84% projects do not meet deadlines and business goals and 78% projects overrun budgets. By paradox, to solve above presented business, economic problem it is necessary to address it by developing axiological research. It is based on the principle that empathy is the third perspective that is build in to the well know Game Theory model which consists of two perspectives: trust and loyalty (Deutsch). In this case, in the process of selecting an appropriate type of the game, between a customer and a vendor, we have to base on a better understanding of needs and axiological profiles on both sites. In other words, if the business goal of the partner is better defined and understood and if it is assumed that the success of one site depends on the other, the final effect, by definition, is almost guaranteed. To achieved that, it is a must for every IT manager to work on developing, the so called business empathy instead of just useless promoting the assertive business philosophy.